2023
DOI: 10.7759/cureus.34221
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir-Associated Acute Liver Failure in a COVID-19 Patient: A Case Report and Literature Review

Abstract: There is a broad classification of the causes of acute liver failure (ALF) that include drug-induced liver injury (DILI). In this report, we aim to discuss the association between remdesivir, a novel therapeutic drug for hypoxic coronavirus disease 2019 (COVID-19) pneumonia, and DILI with subsequent ALF in a patient who was recently treated with the drug in question. Remdesivir, which is a direct-acting nucleoside RNA polymerase inhibitor, is one of the only FDA-approved drugs on the market for COVID-19 pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Some of them have a number of side effects, incl. potential mutagenicity for the host 22 and death 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them have a number of side effects, incl. potential mutagenicity for the host 22 and death 23 …”
Section: Discussionmentioning
confidence: 99%
“…potential mutagenicity for the host 22 and death. 23 WHO recommends medications that inhibit severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) replication, the interleukin-6 receptor, and the tyrosine kinase Janus kinase. 18 Our treatment strategy targets the inhibition of SARS-CoV-2 entry into the cell and the NLRP3 inflammasome, as the source of the CS.…”
Section: Two Different Strategies For Treating Covid-19mentioning
confidence: 99%
“…Several studies have highlighted that there are no absolute contraindications if liver function is closely monitored during treatment [ 60 , 61 ]. Despite a few case reports of suspected remdesivir-associated acute liver failure [ 62 , 63 , 64 ], IDSA guidelines suggest the administration of remdesivir also in hospitalized patients with mild to moderate COVID-19 with a high risk of progression and in patients with severe COVID-19, paying attention to the liver function test. In ambulatory patients, ritonavir could also induce mild to moderate elevation in aminotransferases and cholestasis [ 65 , 66 ].…”
Section: Management Of Covid-19 In Subjects With Fldmentioning
confidence: 99%
“…In early 2020, RDV was approved by the US Food and Drug Administration (FDA) as the first antiviral agent for the treatment of COVID-19 patients requiring hospitalization (Lamb, 2020). Pharmacovigilance data however revealed that clinical use of RDV is associated with potential risk of hepatic adverse drug reactions and monitoring serum levels of ALT and AST has been a required practice in RDV-based COVID-19 treatment (Ahmed-Khan et al, 2023;Aleem et al, 2021;Sadaf et al, 2023). With the rapid evolution of the disease, co-administration of RDV and dexamethasone (DEX) was soon updated as a standard care in the new treatment guideline for hospitalized COVID-19 patients requiring respiratory support (Benfield et al, 2021;Mehta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%